The Behavior of Currencies during Risk-off Episodes - De Bock, Reinout (IMF Working Papers; Working Paper ;, 2013)
Episodes of increased global risk aversion, also known as risk-off episodes, have become more frequent and severe since 2007. During these episodes, currency markets exhibit recurrent patterns, as the Japanese yen, Swiss franc, and U.S. dollar appreciate against other G-10 and emerging market currencies. The pattern of these moves can be explained by a combination of fundamental factors, such as the nominal interest rate, the international investment position and measures of exchange rate misalignment, and market-liquidity factors, such as bid-offer spreads and restrictions on international capital flows. We also find that currency performance in a risk-off episode has become more related to a currency?s yield and relationship to broader risks in recent years.